Profil Psychological Well Being Siswa MTs di Kabupaten Malang - Ninik Trimariya; Blasius Boli Lasan; Nur Hidayah (Pascasarjana UM, 2022)
Abstract: MTs students as teenagers are faced with experiences and challenges as they grow. This study aims to measure the psychological well being of 153 respondents through a survey research design. The instrument used is a psychological well being scale and analyzed through descriptive statistics and graphs. The results showed that the psychological well being condition was in the medium category and tended to be high. Adolescents who have high psychological well being have self-acceptance, Positive relations with others, Autonomy, Environmental Mastery, Environmental Mastery and personal growth. Increasing psychological well being is needed by teenagers. in overcoming challenges in his life, problem solving abilities and optimizing his potential.Abstract: Siswa MTs sebagai remaja dihadapkan pada pengalaman dan tantangan ketika mereka tumbuh. Penelitian ini bertujuan untuk mengukur kondisi psychological well being dari 153 responden melalui desain penelitian survei. Instrumen yang digunakan adalah skala psychological well being dan dianalisis melalui statistik deskriptif dan grafik. Hasil penelitian menunjukkan kondisi psychological well being berada pada kategori sedang dan cenderung tinggi. Remaja yang memiliki psychological well being yang tinggi memiliki penerimaan pada diri sendiri, mampu membina hubungan positif dengan orang lain, memiliki kemandirian, mampu menguasai lingkungan, memiliki tujuan dalam hidup dan pertumbunhan pribadi. Peningkatan psychological well being diperlukan remaja. dalam mengatatsi tantangan dalam hidupnya,kemampuan problem solving dan optimalisasi potensi yang dimilikinya.